2009
DOI: 10.4067/s0718-58392009000200013
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Contamination of Groundwater in a Small Rural Dryland Watershed in Central Chile

Abstract: Research on microbiological groundwater quality was conducted in Chile in a rural watershed that has almost no other water source. Forty-two wells were randomly selected and levels of indicator bacteria -total coliforms (TC), fecal coliforms (FC), and fecal streptococci (FS) -were repeatedly measured during the four seasons of 2005. The aim of this study was to characterize microbiological groundwater quality, relate indicator levels to certain watershed features and management characteristics which are likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 27 publications
0
19
0
3
Order By: Relevance
“…Los autores indican como probables causas de la contaminación, el fácil acceso de animales domésticos a los pozos, el material de revestimiento permeable y el escurrimiento de fecas por la precipitación local, que ha influido directamente en la concentración de bacterias en los pozos 25 .…”
Section: Microbiologíaunclassified
“…Los autores indican como probables causas de la contaminación, el fácil acceso de animales domésticos a los pozos, el material de revestimiento permeable y el escurrimiento de fecas por la precipitación local, que ha influido directamente en la concentración de bacterias en los pozos 25 .…”
Section: Microbiologíaunclassified
“…Previous work has shown that microbiological contamination is dispersed, sporadic, and influenced by a range of interacting environmental factors including the physical characteristics of a watershed, climatic conditions, and agricultural management practices [37]. The influence of human activities on the water quality of the Tibetan Plateau is mostly manifest by production process and day-to-day life; human activities which affect the water quality of the Xincang River Basin mainly include animal husbandry and domestic sewage.…”
Section: Sources Of Microbial Contaminationmentioning
confidence: 99%
“…The main reason for this is that rainfall runoffs carry a lot of microbial contamination sources into the river and cause the increase of microbial concentration in summer. Previous work has shown that microbiological contamination is dispersed, sporadic, and influenced by a range of interacting environmental factors including the physical characteristics of a watershed, climatic conditions, and agricultural management practices [40]. The main bacterial contamination sources in Tibetan Plateau are mostly manifest by production processes and daily life, which mainly include animal husbandry and domestic sewage.…”
Section: Sources Of Microbial Contaminationmentioning
confidence: 99%